ANALISIS PENGARUH MARKETING MIX TERHADAP TINGKAT PENJUALAN PADA CANDU COFFEE DI KOTA PANGKALPINANG - Yoga, Stefanus; Manullang, Rizal Ruben; Panjaitan, Fery (Jurnal Progresif Manajemen Bisnis, 2023)
The theories used in this study are management theory, management functions, management as a science, marketing theory, marketing definitions, marketing management functions, marketing management objectives, marketing strategy, marketing mix. Therefore, Candu Coffe must always focus on product quality, price, place and promotion to increase sales levels. The coconut tree technique was used to obtain 101 samples from a population of 257, an appropriate sample selection method was needed. One method commonly used is simple random sampling. The results of this study indicate that the Adjusted R2 is 0.612. The adjusted R2 value can be defined as 61.2%. It can be concluded that the independent variables including product, price, place and promotion can explain and affect the dependent variable the sales level of 61.2%. The remaining 38.8% can be explained by other variables not used in this study. The first hypothesis from H1 shows a positive and significant t-value. This matter. This means that individually (partial) product variables have a positive and significant effect on the level of sales at Opium Coffee in Pangkalpinang City. H1 is accepted with a value of: 3.679 and P-Value <.001. The second hypothesis of H2 shows a negative and significant value. This matter. This means that the t test obtained individually (partial) the price variable has a negative and significant effect on the level of sales at Candu Coffee in Pangkalpinang City. The accepted H2 is with a value of: (-3.523) and P-Value <.001. The third hypothesis from H3 shows a positive and significant t-value. This matter. This means that individually (partial) place variables have a positive and significant effect on the level of sales at Opium Coffee in Pangkalpinang City. H3 is accepted with a value of: 5.395 and P-Value <.001. The fourth hypothesis from H4 shows a positive and significant t-value. This matter. This means that individually (partial) the promotion variable has a positive and significant effect on the level of sales at Opium Coffee in Pangkalpinang City. The H4 received is with a value of: 2.189 and a P-Value of 0.031. The fifth hypothesis of the F test states that the value is obtained product, price, place, and promotion have a positive and significant effect on the level of sales. At Candu Coffee in Pangkalpinang City, the H5 received is with a value of: 40.363 and P-Value <.001.